Geophysical threats of wartime to high-risk objects of Ukraine - Anakhov, P.V. (Geofizicheskiy Zhurnal, 2022)
Environment is changed by man consciously and mostly unconsciously. A characteristic feature of modern times is the unprecedented number of potentially dangerous enterprises that pose a real threat of emergencies of natural and man-made origin. Accidents at 203 high-risk Ukrainian facilities can lead to emergencies at the regional and state levels, spreading to other countries. Of all human engineering activities, hydraulic engineering has the greatest impact on the natural environment; significant effects of artificial regulation of precipitation, mining. These actions may also have military uses that involve intentional harm. The main task of military hydraulic engineering is the creation of artificial water barriers to advance the enemy. The use of artificial rainfall for the same purpose helps to soften road surfaces and provokes landslides along them, supports the erosion of river fords and increased soil water saturation. The earthquakes caused by the bombings are causing extensive damage to infrastructure. At the end of February 2014, Russia launched hostilities in Ukraine, which began with the annexation of Crimea, continued with a protracted armed conflict in the Donetsk and Luhansk regions, led to the entry of troops on February 24, 2022. Military action is accompanied by conscious and unconscious manifestations of aggression in potentially dangerous enterprises. To protect against natural disasters of anthropogenic origin, in 1976 the Environmental Modification Convention was adopted. To date, only 94 of the 193 UN countries have ratified or agreed to the Convention. The list of potential 99 violators is supplemented by the founding member states of the United Nations and initiators of the development of the Convention within the USSR, the Russian Federation, which is waging hostilities on the territory of Ukraine, and Belarus.